IT Helpdesk Ticketing System Berbasis Web Pada Bagian ERP (Enterprise Resource Planning) PT Perkebunan Nusantara VI - Fadillah Effendi, Husnil; Assegaff , Setiawan (Jurnal Manajemen Sistem Informasi, 2022)
PT Perkebunan Nusantara VI is one of the companies operating in the plantation sector that is transforming the development of information technology to help improve the efficiency and effectiveness of the company. PT Perkebunan Nusantara VI has an ERP section that is implementing changes to business processes, initially all transactions were recorded manually and now all transactions are recorded through the SAP application system which makes all parts of PT Perkebunan Nusantara VI integrated in real time. In the implementation of the SAP application at PT Perkebunan Nusantara VI it did not go well where many human resources did not understand SAP technology and there were many data input errors that made errors in transactions and errors in the SAP application system, based on these conditions, a system is needed that can assist in handling of every problem that exists in every part of PT Perkebunan Nusantara VI so that the handling is more well structured and also helps in the reporting system. So the final result of this research is a proposed helpdesk ticketing system application that makes it easier for the reporting system and handling problems that exist in the transaction process in the SAP application.